IMPACTS OF CLIMATE VARIABILITY ON SUSTAINABLE AGRICULTURAL WATER MANAGEMENT IN YAURI, NORTHWESTERN, NIGERIA - Ahmad, Lawal; Adigun, Habeeb Adekunle; Aliyu, Muzzamil; Wakawa, Daniel Thlama; Damana, Usman Muhammad (FUDMA Journal of Sciences, 2025)
Climate variability is greatly affecting water management and agricultural productivity particularly in semi-arid region like Yauri which experiences both flood and drought. This study examines the impacts of climate variability on sustainable agricultural water management in Yauri, Northwestern, Nigeria, using 30 years of meteorological data integrated with field surveys of agricultural water management practices. Descriptive statistics, including the Precipitation Concentration Index (PCI), Temperature Anomaly Index (TAI), Mann-Kendal trend test, and Sen’s Slope Estimator were applied to assess rainfall and temperature variability, trends, and anomalies. Total seasonal rainfall, onset, cessation, and length of growing season were also analyzed to determine implications for agricultural water use. Results show an average annual rainfall of 110.3 mm with 20.49 % coefficient of variation, indicating moderate variability. The rainy season lasted 135-178 days (average 164 days). PCI values (16.30-23.81) indicated moderate to irregular rainfall distribution, while trend analysis revealed a slight but statistically insignificant rise in seasonal rainfall ( . Temperature trends show a significant increase in minimum temperature (+0.074 , p
Keywords: Climate change; Sustainable Agriculture; Water Management; Yauri; Nigeria